Drying Grapes after the Application of Different Dipping Solutions: Effects on Hormones, Minerals, Vitamins, and Antioxidant Enzymes in Gök Üzüm (Vitis vinifera L.) Raisins - Nurhan Keskin; Ozkan Kaya; Fadime Ates; Metin Turan; Gastón Gutiérrez-Gamboa (Plants, 2022)
(1) Background: Raisins contain a wide range of hormones, minerals, vitamins, and antioxidant enzymes that may contribute to the health benefits of consumers. (2) Methods: The aim of this research was to compare the hormone, mineral, vitamin, and antioxidant capacities of Gök Üzüm (Vitis vinifera L.) raisins immersed in oak ash (OA) and potassium carbonate (PC) dipping solutions before drying. (3) Results: Abscisic acid (ABA) (5751.18–11,868.40 ng g−1) and riboflavin (95.17–135.54 mg 100 g−1) were the most abundant hormone and vitamin quantified in Gök Üzüm raisins. Glutathione S-transferase (540.07–744.85 EU gr berry−1), 6-glucose phosphate dehydrogenase (214.50–317.43 EU gr berry−1), and glucose-6-phosphate dehydrogenase (208.25–241.86 EU gr berry−1) enzymes presented the highest antioxidant activity in the samples. Raisins obtained after drying by immersion in OA presented higher indol-3-acetic acid (IAA), ABA, salicylic acid (SA), cytokinins (CK), and zeatin contents; glutathione reductase (GR), glucose-6-phosphate dehydrogenase (G6PD), glutathione S-transferase (GST), 6 glucose phosphate dehydrogenase (6GPD), catalase (CAT), peroxidase (POD), and superoxide dismutase (SOD) enzymatic activity; vitamin B1, B2, B6, C, and A contents; and nitrogen (N), phosphorus (P), manganese (Mn), calcium (Ca), sulfur (S), potassium (K), iron (Fe), sodium (Na), and magnesium (Mg) levels compared to the grapes dried after PC applications. (4) Conclusions: Drying Gök Üzüm grapes after the application of OA dipping solution promotes a higher content of hormones, minerals, vitamins, and antioxidant enzymes compared to PC treatments. These results could help raisin producers to make decisions when using a dipping solution to dry grapes.